Twisted Laguerre-Gaussian mode division multiplexing to support blockchain applications - Hassan, Suhaidi; Fazea, Yousef; Habbal, Adib M. Monzer; Ibrahim, Huda (2017)
The blockchain is a distributed ledger shared among computers around the world that allowing anyone to transact and do business with each other.Once a new block is created, ledger's transactions are updated and synchronized.Hence, the speed of information propagation in order to minimize the time taken by a node to verify a block before announcing it to the network is very significant that should be leveraged by the enabling technologies.However, due to the huge of data capacity needed, mode division multiplexing (MDM) is a promising approach to provide an additional level of freedom through propagating different channels in multimode fiber (MMF). Nevertheless, mode coupling is considered as the primary bandwidth impairment of MMF due to the mode's random perturbation. This paper investigates the potential of mode spacing in conjunction with a feed-forward equalizer on twisted Laguerre-Gaussian (LG) MDM.Free error transmission of 40Gbit/s over MMF is achieved. The bit-error-rate and eye diagram have been used as a measurement metrics.